A raciolinguistic analysis of the neoliberal promotion of dual language education in a new Latinx South state. Issue 1 (2nd January 2023) - Sun, Wenyang; Wang, Xinxin
ABSTRACT: Dual language (DL) programs in the United States are increasingly promoted as a promising model that serves both language majority and minoritized children. However, many researchers also question whether the programs are truly serving the language minoritized students, or are these programs only treating their language as a resource to serve the already privileged group. Using structural topic modeling and critical discourse analysis, this study employs a raciolinguistic perspective to unpack the ideologies underlying the discourses in over 200 DL programs in a new Latinx South state of the United States. Our findings show that DL programs are promoted as a model that brings cognitive and employment benefits to its students. Moreover, private corporate power has a strong existence and influence on the establishment, staffing, and promotion of DL programs. The benefits to English speaking students are highlighted, while the interests of language minoritized children are largely ignored in the discourse.